Make It Now : New Sculpture In New York. - Ceruti, Mary; Huberman, Anthony; Sirmans, Franklin (New York : SculptureCenter New York, 2005)
Benson, Frank W. ; Cherubini, Nicole ; Cohen, Andrea ; Foos, Charlie ; Gispert, Luis ; Guyton & Walker ; Hardy, Dave ; Harrison, Rachel ; Hewitt, Leslie ; Hohza, Klara ; Hwang, Nancy ; Jackson Hutchins, Jessica ; James, Gareth ; Mazeau, Vincent ; McCorkle, Corey ; Melee, Robert ; Norling, Navin June ; Partegas, Ester ; Price, Seth ; Ronay, Matthew ; Savitz, Bryan ; Shin, Jean ; Sibony, Gedi ; Sigal, Lisa ; SOL'SAX ; Visani, Roberto ; Washburn, Phoebe ; Welch, Fritz
biog., tent. per kunstenaar
Engels
Exhibition. Make It Now : New Sculpture In New York. SculptureCenter New York. 15.05.2005 - 31.07.2005.
boek
Keywords: New York